A preventing method for overlapping focuses in a Focus+Glue+Context Map. (19th March 2013) - Mizutani, Hiroya; Yamamoto, Daisuke; Takahashi, Naohisa
We have previously developed a Focus+Glue+Context–type fisheye view map system called Emma. Emma shows maps of different scales on the same display region, so that users can use wide maps (Context) and confirm details (Focuses) simultaneously. However, when multiple Focuses overlap, Emma is problematic in that road–network connections cannot be correctly drawn. In this paper, we propose the Water Drop method as a solution to this problem. It prevents overlapping by transforming Focuses much in the same way that drops of water are transformed, united, and divided due to surface tension. In order to prove the efficiency of the proposed method, we also developed the Overlap Repulsion method as a baseline approach. It prevents overlapping by moving the inactive Focuses away from the active Focus when an active Focus overlaps inactive Focuses. We conducted three experimental evaluations from the point of view of the both usability of the interface and map visibility.